Analisis Faktor - Faktor Yang Mempengaruhi Loyalitas Merek Pada Kain Tenun Lurik "Prasojo" (Pt. Kusumatex, Pedan) - Wijayati, Didien Jatu (2016)
The purpose of this study was to analyze the effect of customer loyalty as well as the factors that influence other customers , let alone on the brand and the product price . So customers both from middle - and upper vying to wear and become a loyal customer of the product " Prasojo " in the middle of prey market exists today, in times of batik cloth is still very desirable and familiar . Especially in this Soloraya own Batik Laweyan still a trend and competitor that needs attention . The sample in this study were all customers Lurik fabrics Prasojo by 55 respondents . Methods of data analysis using multiple linear regression test , F test , t praise and test the coefficient of determination . Using the classical assumption of normality test , multicollinearity and heteroscedasticity . The results showed that 1) The test results are known tcount t> t table or 2.545> 2.015 with 0.014 significance value <0.05. This means that H0 is rejected at the 0.05 significance level. This means that the variable quality of the effect on customer satisfaction, 2) test results are known tcount t> t table or 2.398> 2.015 with 0.021 significance value <0.05. This means that H0 is rejected at the 0.05 significance level. This means that the price variable effect on customer satisfaction, 3) The t test result is known tcount> ttabel or 2,449> 2,015 with significant value 0.018> 0.05. This means that H0 is accepted at significance level of 0.05. This means that brand variable effect on customer satisfaction, 4) The test results are known tcount t> t table or 3.057> 2.015 with 0.004 significance value <0.05. This means that H0 is rejected at the 0.05 significance level. This means service variable effect on customer satisfaction; 5) The test results are known tcount t> t table or 3.222> 2.015 with 0.002 significance value <0.05. This means that H0 is rejected at the 0.05 significance level. This means that the image variable effect on customer satisfaction. Based on the results of the F test is concluded that the variable quality ( X1 ) , Price ( X2 ) , Brand ( X3 ) , Services ( X4 ) , and Citra ( X5 ) have influence simultaneously to variable customer satisfaction ( Y ) , it is evident from the results regression analysis of known value of F > F table ( 15.745 > 2.427 ) . Keywords : quality , price , brand , service , image and customer satisfaction .